Konsistensi Keberadaan Asas Lex Specialis De Rogat Lex Generalis dalam KUHP Nasional - Fadlly Fadlly; Muhammad Zulfian Ramadhan; Fuad Nur (Jejak digital: Jurnal Ilmiah Multidisiplin, 2026)
The enactment of the National Criminal Code through Law Number 1 of 2023 represents a fundamental reform in the Indonesian criminal law system. One of the crucial issues arising from this reform concerns the consistency of the existence of the principle of lex specialis derogat lex generalis in relation to special criminal laws that have developed outside the Criminal Code. This principle theoretically functions as a guideline for resolving normative conflicts between general criminal law provisions and special criminal law provisions. This study aims to analyze the consistency of the regulation and application of the lex specialis derogat lex generalis principle within the National Criminal Code and its implications for the applicability of special criminal laws. The research employs normative legal research using statutory and conceptual approaches. The findings indicate that although the National Criminal Code normatively positions itself as general criminal law (lex generalis), there are regulatory dynamics that may affect the application of the lex specialis principle, particularly in its relationship with special criminal legislation. Therefore, systematic interpretation and normative harmonization are required to ensure the consistent application of the lex specialis derogat lex generalis principle in the national criminal law system in order to guarantee legal certainty and effective law enforcement..